Análise da percepção de mães brasileiras e americanas em relação à influência da publicidade em canais do YouTube nas escolhas de consumo do público infantil - Mascarello, Camila Cinelli (My University, 2019)
Child consumption is growing worldwide and it is increasingly common to see products and services designed exclusively for children. The tools used to attract children have the most varied molds, however currently stand out the options related to digital marketing. For this reason, this research aimed to analyze advertising on YouTube channels and the purchase decision of the American and Brazilian child consumers. The method chosen for the research was a qualitative exploratory study, with the application of twelve interviews, six of them with mothers of Brazilian children and another six with mothers of American children. For the application of the interviews, a semi-structured script was prepared, which allowed the researcher to investigate the perception of Brazilian and American mothers about the main characteristics related to the influence of YouTube channel advertising on their children's consumption choices. Through the interviews, it was possible to show that there is a great difference in the consumption on YouTube by American and Brazilian children. The first great distinction is the favorite content, since in the perception of American mothers the educational theme is the one with the largest audience among children and, in the perception of Brazilian mothers, videos related to activities and challenges are favorites of the children. In addition, it could be noted that the advertising effects are also different. In the perception of American mothers, children are not influenced by YouTube and any kind of advertising. However, Brazilian mothers stated that advertising inserted mainly within the platform awakens the desire for consumption in children.(sic)
O consumo infantil vem crescendo no mundo inteiro e é cada vez mais comum observar produtos e serviços destinados exclusivamente para as crianças. As ferramentas utilizadas para atrair as crianças apresentam os mais variados moldes, no entanto atualmente destacam-se as opções relacionadas ao marketing digital. Por esse motivo, a presente pesquisa teve como objetivo analisar a publicidade em canais do YouTube e a decisão de compra do consumidor infantil americano e brasileiro. O método escolhido para a realização da pesquisa foi um estudo qualitativo de caráter exploratório, com a aplicação de doze entrevistas, sendo seis delas com mães de crianças brasileiras e outras seis com mães de crianças americanas. Para a aplicação das entrevistas, foi elaborado um roteiro semiestruturado, que permitiu à pesquisadora investigar a percepção das mães brasileiras e americanas sobre as principais características relacionadas à influência da publicidade de canais do YouTube nas escolhas de consumo de seus filhos. Através das entrevistas, foi possível evidenciar que existe uma grande diferença no consumo no YouTube por crianças americanas e brasileiras. A primeira grande distinção são os conteúdos preferidos, já que na percepção das mães americanas a temática educativa é a de maior audiência entre as crianças e, na percepção das mães brasileiras, os vídeos relacionados a atividades e desafios são os favoritos do público infantil. Além disso, pôde-se notar que os efeitos publicitários também são diferentes. Na percepção das mães americanas, as crianças não são influenciadas pelo YouTube e por nenhum tipo de propaganda. Porém, as mães brasileiras afirmaram que a publicidade inserida principalmente dentro da plataforma desperta o desejo de consumo nas crianças.(sic)
Keywords: Publicidade; Consumo (Economia); Marketing